Zakaj uživa pomorski prevoznik ugodnejši režim odgovornosti v primerjavi s prevozniki iz drugih panog - Vlačič, Patrick (Pravnik, 2016)
The purpose of this paper is to answer the question: Why is there a different liability of the carrier in maritime carriage of passengers and goods in comparison to other transport modes? Except in the EU countries and a small number of others, a maritime carrier's liability for damages that were suffered by passengers is fault. There is different liability of the carrier in air, rail and road transport, where liability is strict. No serious discussions regarding the maritime carrier's liability in terms of bringing about unity with the others means of transport have been held, nor any theories in that regard put forth. Determining the cause of this exception for the maritime sector's liability is a difficult task. Scholars worldwide record the situation without any apparent investigation into its origin. Is there a serious and justifiable reason for such a special liability regime for maritime transport or is this merely a consequence of the current balance of power of players in maritime transport, or perhaps even an historical relict? This article was created in order to provide an answer to this intriguing question.
Keywords: odgovornost; pomorski promet; potniški promet; pravna ureditev